Digitalization In Scanning And Remote Shutdown Host of Computer Using Apache Cordova Framework - Sukmana, Farid; Rozi, Fahrur (STKIP PGRI Tulungagung, 2019)
Internet of Things is one concept in technology 4.0, this technology combine of two component, that is internet and mechine. Internet use to send signal from mechine to second device like mobilephone or from the mobilephone to mechine to execution task. Information Technnology infrastructure in industrial company has many complexity in network, hardware, or software. Especially for hardware like desktop computer or laptop, ech employee has one of them. And many of them, sometime forget to shutdown they computer or they has purpose did not shutdown they computer just for download the big file. Indirectly, the computer that run more than 24 hours in industrial company, it will be degrade service of life, and the consumption of electricity need the high cost. In this paper, our purpose is how to reduce computer that not needed run 24 hours can be monitor and can be shutdown in the out of company area. This is need concept of internet of things and digitalitation to make it. For this problem can be used monitoring system by mobile application, this system will be show about the host computer still be on, and can be remote shutdown with mobile device. This application use cordova to build it and the command from mobile be send to server to shutdown computer that still online.Â